Sun in the religious life and Lore of India - Mohanty, Muralidhar 1931- (Kolkata Punthi Pustak, 2006)
Based on Vedic literature
Includes bibliographical references and index
Includes passages in Sanskrit; (Sanskrit in roman)
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Sūrya -- (Hindu deity) -- Cult -- India; Vedic literature -- History and criticism